1999
DOI: 10.1002/(sici)1521-3935(19990501)200:5<1062::aid-macp1062>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Monomers for adhesive polymers, 2. Synthesis and radical polymerisation of hydrolytically stable acrylic phosphonic acids

Abstract: SUMMARY: Acrylic groups containing phosphonic acids were synthesised by ether formation of ethyl achloromethylacrylate with hydroxyalkylphosphonates and subsequent hydrolysis to the corresponding phosphonic acid a-methyl-substituted acrylates. The structure of the synthesised monomers was confirmed by elemental analysis, IR, 1 H NMR, 13C NMR and 31 P NMR spectroscopy. The monomers are stable in aqueous ethanol. The radical polymerisation of the monoacrylates in tetrahydrofuran with 2,29-azobisisobutyronitrile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 6 publications
0
70
0
1
Order By: Relevance
“…The reactions of bis(trimethylsilyl) phosphonates with alcohols leads to the corresponding phosphonic acid and alkoxytrimethylsilane [10] in a fast reaction. [11] Use of the trimethylsilyl esters thus allows generation of the phosphonic acid in situ, which may substitute some of the OiPr groups of Ti(OiPr) 4 . The (coordinated or noncoordinated) phosphonic acid could then react with 2-propanol, possibly catalyzed by Ti(OiPr) x moieties, [12] to produce water for condensation and the observed isopropyl monoester.…”
Section: Resultsmentioning
confidence: 99%
“…The reactions of bis(trimethylsilyl) phosphonates with alcohols leads to the corresponding phosphonic acid and alkoxytrimethylsilane [10] in a fast reaction. [11] Use of the trimethylsilyl esters thus allows generation of the phosphonic acid in situ, which may substitute some of the OiPr groups of Ti(OiPr) 4 . The (coordinated or noncoordinated) phosphonic acid could then react with 2-propanol, possibly catalyzed by Ti(OiPr) x moieties, [12] to produce water for condensation and the observed isopropyl monoester.…”
Section: Resultsmentioning
confidence: 99%
“…Further, it was found that a self-etching primer comprising 10-MDP provided efficient bonding of composite-type resin cement to titanium (Ti) 42) , while an adhesive primer containing 6-MHPA was found to exhibit strong adhesion to zirconia-and alumina-based all-ceramic prostheses 43) . On this note, hydrolytically stable adhesive monomers should be incorporated in single-bottle water-based self-etch primers or all-in-one adhesives [7][8][9][10][11][12][13] . In addition to phosphonic acid and flexible methylene chain moieties, it was suggested that a super-adhesive monomer should possess hydrolytically stable moieties in the molecular structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, they formulated with ethyl alcohol, and did not show significant efficacy on bonding to the teeth 6) . Despite the lack of early success, recently synthesized phosphonic acid monomers appeared to be hydrolytically stable in self-etching primers or adhesives [7][8][9][10][11][12][13] and hence seemed promising. However, since these investigations [7][8][9][10][11][12][13] have not been extended beyond water-based adhesives, little is known about the multi-purpose bonding performance of phosphonic acid monomers with polymerization initiators in hydrophobic adhesive resins.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of monomers was described elsewhere. [24] The structure of Me-PAMA 18 is shown in Figure 1b.…”
Section: Methodsmentioning
confidence: 99%